OPTIMASI PENEMPATAN ALAT-ALAT UKUR UNTUK PERINGATAN DINI BANJIR LAHAR - , Eko Sulistyo; , Ir. Adam Pamudji, M.Sc, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The eruption of Merapi volcano to leave a deposit so much sediment around the slopes of Merapi volcano, and this can lead to a debris flow that trigger is heavy rainfall. To reduce the risk due debris flow, early warning system is needed that can provide accurate data on the time of occurrence of the debris flow. Rainfal lmeasuring devices very important role as an input for an early warning system. Placement of rain gauge is sometimes not optimal, so that the data from rain gauge, less represents the actual situation on the field. As a result of input for an early warning system to be less accurate, therefore, its necessary for the optimization of the placement of the rain gauge. Optimization is done by dividing the watershed that could be potentially the location of the placement of rain gauge to 15 cell cluster. The sized of cell is 1,5x1,5 Km. Each of these cells will have information in the form of three objective functions such as the percentage bias (PBIAS), normalized mean square (NMSE), and the coefficient of the third correlation from objective function is compromised to get close to the ideal value. The placement of the rain gauge at cells whose value is close to the ideal. The results of the 15 cells optimization potential placement locations for configuration 1 rain gauge station located at the coordinates 7° 35' 0,180\" S, 110° 22' 37,177\" E. Configuration of 2 rain gauges at coordinates 110° 21' 48,226\" E, 7° 35' 0,109\" S and 110° 24' 15,213\" E, 7° 33' 22,628\" S. Configuration 3 rain gauges at coordinates 110° 20' 10,250\" E, 7° 35' 48,806\" S , 110° 22' 37,247\" E, 7° 34' 11,336\" S dan 110° 25' 4,227\" E, 7° 32' 33,850\" S. Optimum number is configuration of 2 rain gauges station. Keywords: optimization, rain gauge, early warning, debris flow